Sosial Budaya dan Dinamika Pemilihan Temenggung Suku Anak dalam (SAD) Secara Adat di Komunitasnya pada Dusun Dwi Karya Bhakti Kecamatan Pelepat, Bungo - Joko Setyoko; Ronal Dison; Jenderi Halis Saputra (Universitas Muara Bungo, 2023)
The Anak Dalam tribe or known by another name SAD is a native Indonesian tribe that spreads across the island of Sumatra, this tribe itself has special characteristics in its habits and way of life. SAD itself is a marginalized tribal group and spends much of its life in the forest, but that's not the case. This means that Sad does not have leadership regulations. In each SAD group there is one leader known as Temenngung. This temenggung leadership period itself does not have part time or has no leadership period limits. For this reason, Sad can be said to be a group that adheres to a chain of command or bureaucracy in its leadership because this is proven by its form of leadership and procedures for selecting the group leader or temenggung. The origins of Sad Sndri are native people from West Sumatra, specifically Pagaruyuh, who fled into the forest because of past wars in Indonesia, therefore SAD depends on hunting and relying on garden products for its living. However, in the current era, Sad is crawling to follow the life of the general public with several tips and assistance from the regional government so that now Sad lives like the general public who live by relying on the agricultural sector, trade and state servants. In selecting the temenggung as their leader, there are stages that must be passed, and these stages have become institutionalized. This is the reference point for today's ethnic groups.